PENGARUH PENGANGGURAN DAN BELANJA PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Muhammad Rizky; Ikhsan Ikhsan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract The study aims to analyze the effect of unemployment and government spending on economic growth in Indonesia, because the unemployment rate in Indonesia is still too high while government spending always increases every year, while economic growth never reaches the target set by the government so wants to do this research the effect of unemployment and government spending on economic growth in Indonesia. Data for this study uses secondary data. The variables used in this study, namely: variable unemployment rate, government spending variable, and economic growth variable. The analysis model used in the study is a multiple linear regression model with data from 2000 to 2017. The results of this study indicate that the unemployment rate variable has a significant and negative effect on the variable economic growth, while the government expenditure variable has a positive and significant effect on the variable economic growth .Keywords: Unemployment, Government Expenditures, Economic Growth.